Evaluating Acupuncture and Standard carE for pregnant women with Back pain (EASE Back): a feasibility study and pilot randomised trial - Nadine E Foster; Annette Bishop; Bernadette Bartlam; Reuben Ogollah; Panos Barlas; Melanie Holden; Khaled Ismail; Sue Jowett; Christine Kettle; Jesse Kigozi; Martyn Lewis; Alison Lloyd; et al. (Health Technology Assessment, 2016)
Background: Many pregnant women experience low back pain. Acupuncture appears to be a safe, promising intervention but evidence is needed about its clinical effectiveness and cost-effectiveness. Objectives: To assess the feasibility of a future large randomised controlled trial (RCT) testing the additional benefit of adding acupuncture to standard care (SC) for pregnancy-related back pain. Design: Phase 1: a questionnaire survey described current care for pregnancy-related back pain. Focus groups and interviews with midwives, physiotherapists and pregnant women explored acceptability and feasibility of acupuncture and the proposed RCT. Phase 2: a single-centre pilot RCT. Participants were identified using six methods and randomised to SC, SC plus true acupuncture or SC plus non-penetrating acupuncture. Participants: Phase 1: 1093 physiotherapists were surveyed and 15 midwives, 21 physiotherapists and 17 pregnant women participated in five focus groups and 20 individual interviews. Phase 2: 125 women with pregnancy-related back pain participated. Interventions: SC: a self-management booklet and onward referral for one-to-one physiotherapy (two to four sessions) for those who needed it. SC plus true acupuncture: the self-management booklet and six to eight treatments with a physiotherapist comprising true (penetrating) acupuncture, advice and exercise. SC plus non-penetrating acupuncture: the self-management booklet and six to eight treatments with a physiotherapist comprising non-penetrating acupuncture, advice and exercise. Main outcome measures: Pilot RCT outcomes included recruitment rates, treatment fidelity, follow-up rate, patient-reported pain and function, quality of life and health-care resource use. Birth and neonatal outcomes were also assessed. Staff overseeing outcome data collection were blind to treatment allocation. Results: Phase 1: 629 (57.5%) physiotherapists responded to the survey, 499 were experienced in treating pregnancy-related back pain and reported 16 advice and 18 treatment options. Typical treatment comprised two to four individual sessions of advice and exercise over 6 weeks. Acupuncture was reported by 24%. Interviews highlighted the impact of back pain and paucity of effective interventions. Women and midwives strongly supported a RCT and expressed few concerns. Physiotherapists’ concerns about acupuncture in pregnancy informed a training programme prior to the pilot RCT. Phase 2: We recruited 125 of 280 potentially eligible women (45%) in 6 months and randomised 41 to SC and 42 each to the SC plus true acupuncture and SC plus non-penetrating acupuncture arms. Analysis was conducted with 124 participants (41, 42 and 41, respectively) as one participant was randomised in error. Three of six recruitment methods were the most successful. In total, 10% of women (n = 4) randomised to SC alone accessed one-to-one physiotherapy and received an average of two treatments. The average number of treatments was six for both SC plus true acupuncture and SC plus non-penetrating acupuncture. Treatments were in line with protocols. Eight-week follow-up was 74%. Patient-reported outcomes (pain, function and quality of life) favoured the addition of acupuncture. There was no evidence of serious adverse events on mothers or birth and neonatal outcomes. The Pelvic Girdle Questionnaire was found to be an appropriate outcome measure for a future trial. Conclusions: A future main RCT is feasible and would be welcomed by women and clinicians. Longer-term follow-up and further follow-up efforts are recommended for a main trial. Trial registration: Current Controlled Trials ISRCTN49955124. Funding: This project was funded by the National Institute of Health Research Health Technology Assessment programme and will be published in full in Health Technology Assessment; Vol. 20, No. 33. See the NIHR Journals Library website for further project information.